Growth and Carcass Physical Components of Thin Tail Rams Fed on Different Levels of Rice Bran - Rianto, E; Lindasari, E; Purbowati, E (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
This experiment was aimed to investigate the effect of rice bran supplementation on live weight gain (LWG), the proportion of carcass meat, bone and fat of Thin Tail Rams. Twelve thin tail rams, aged about 12 months, weighed 20.95 Â± 1.52 kg (CV = 7.26%) were allocated into a Randomized Block Design with 2 blocks and 3 treatments. The treatments applied were levels of rice bran supplementation, i.e. Napier grass ad libitum without rice bran (T1), Napier grass ad libitum and 200 g rice bran (T2) and Napier grass ad libitum and 400 g rice bran (T3). The results showed thatÂ rice bran supplementation highly significantly (P<0.01) increased liveweight gain, hot and cold carcass weight. The treatment applied also significantly (P<0.05) increased slaughter weight, hot and cold carcass percentage, and carcass meat weight. However, the treatments did not significantly (P>0.05) influence the percentage of carcass meat and bone percentage. It was concluded that rice bran supplementation increased slaughter weight, carcass weight and carcass percentage, carcass meat and bone weight, and carcass fat percentage, but did not influence the percentage of carcass meat and carcass bone. (Animal Production 8(1): 28-33 (2006)Â Key Words : Thin Tail Rams, rice bran, carcass physical components.